PENGEMBANGAN EKOWISATA BERWAWASAN KEARIFAN LOKAL DI WILAYAH EKS KARESIDENAN BESUKI, JAWA TIMUR - Mastika, I Ketut (Jurnal Master Pariwisata (JUMPA); Volume 04, Nomor 02, Januari 2018DO - 10.24843/JUMPA.2018.v04.i02.p06, 2018)
The objective of this study is to channel creative potential in creating an eco-tourism. The research was carried out in the area a national park in the region of the ex Besuki Residency, East Java. This study used ethical and emic perspectives. The results show that the development of responsible and sustainable of eco-tourism require gure of mobilisers, community togetherness, public appreciation of the natural resources, community openness to receive visitors, the growth of natural-based creative economy sectors, and the government’s attention in providing infrastructure especially for accessibility. The novelty of this study is the importance of understanding the development of eco-tourism which is based of creative instinct, appreciating local wisdom’s values, understanding, comprehending and embracing the meaning and essence of keeping the relationship between humans and humans, nature and the Creator in balance. Intellectual capability with local indigenous power is such the main factor for a responsible, bene cial, and sustainable development of eco-tourism.